ESRA19-0530 Onvision™ needle tip tracking using ultrasound imaging for out-of-plane lumbar plexus blocks – a first in human volunteer study. (30th August 2019) - Kåsine, T; Romundstad, L; Rosseland, LA; Ullensvang, K; Fagerland, MW; Kessler, P; Sauter, AR
Abstract : Background and aims: The Onvision™ is a new technology for needle tip tracking (NTT). The technology makes use of a piezoelectric sensor on the needle tip that is represented by a green circle on the ultrasound screen (figure 1 ). In a phantom study NTT significantly reduced the procedure time for out-of-plane simulated blocks (Kåsine et al. 2019). The aim of this study was to investigate the effect of NTT on procedure time and hand motion analysis in a first-in-human volunteer study. Methods: This was a randomised, controlled, crossover study in healthy volunteers. Two anaesthesiologists performed lumbar plexus blocks with an out-of-plane approach using Karmakar's trident technique. 27 volunteers received blocks with and without Onvision™ NTT using 20 ml lidocaine 20 mg/ml with adrenaline. Procedure time was the primary outcome. Number of hand movements and path length were measured by motion analysis. Other secondary outcomes were block success, onset time, block duration, discomfort experienced by the volunteers, and the anaesthesiologists' confidence in block success. Results: We found a statistically non-significant reduction in procedure time when NTT was used (table 1 ). Decreased numbers of intended hand movements and path lengths were found for the needling hand. No significant differences were found for other secondary outcomes. Mild adverse events included high unilateral epidural spread (one volunteer; without NTT) and systemic toxicity of local anaesthetics (one volunteer; with NTT). Conclusions: NTT significantly reduced the number of hand movements (34%) and path lengths (44%). This indicates improved needle control. The reduction in procedure time with NTT was statistically non-significant.